Dental Care for Patients with End-Stage Renal Disease and Undergoing Hemodialysis - Fulvia Costantinides; Gaetano Castronovo; Erica Vettori; Costanza Frattini; Mary Louise Artero; Lorenzo Bevilacqua; Federico Berton; Vanessa Nicolin; Roberto Di Lenarda (International Journal of Dentistry)
Chronic renal failure is a progressive disease characterized by a gradual destruction of nephrons and a consequent reduction of kidney function. End-stage renal disease (ESRD) necessitates renal replacement therapy as peritoneal dialysis, hemodialysis, or transplantation. Patients affected by ESRD or in hemodialysis are at risk for developing a number of comorbidities including hypertension, anemia, risk of bleeding, susceptibility to infection, medication side effects, and oral manifestations associated with the disease itself and with hemodialysis treatment. In this context, oral diseases represent a potential and preventable cause of poor health outcomes in people with ESRD due to their relation to infection, inflammation, and malnutrition. The aim of this article was to review ESRD and hemodialysis-associated manifestations and to describe the dental operative protocols for patients awaiting kidney transplantation in light of the most recent literature.